2019
DOI: 10.1101/579045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient parameterization of large-scale dynamic models based on relative measurements

Abstract: Motivation: Mechanistic models of biochemical reaction networks facilitate the quantitative understanding of biological processes and the integration of heterogeneous datasets.However, some biological processes require the consideration of comprehensive reaction networks and therefore large-scale models. Parameter estimation for such models poses great challenges, in particular when the data are on a relative scale.Results: Here, we propose a novel hierarchical approach combining (i) the efficient analytic eva… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Leaving aside the even more complicated task of network inference, parameter optimization and uncertainty analysis are currently the key challenges for large-scale models, for which no satisfactory approaches exist. Due to the high computation times, toolboxes suitable for computing clusters are necessary and have recently been developed (Penas et al, 2017;Schmiester et al, 2019). Moreover, new approaches have to be explored, such as transferring the concept of mini batching from the field of deep learning to optimization (Goodfellow et al, 2016) or MCMC sampling (Seita et al, 2017) of dynamic models, and must be adapted to ODE models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leaving aside the even more complicated task of network inference, parameter optimization and uncertainty analysis are currently the key challenges for large-scale models, for which no satisfactory approaches exist. Due to the high computation times, toolboxes suitable for computing clusters are necessary and have recently been developed (Penas et al, 2017;Schmiester et al, 2019). Moreover, new approaches have to be explored, such as transferring the concept of mini batching from the field of deep learning to optimization (Goodfellow et al, 2016) or MCMC sampling (Seita et al, 2017) of dynamic models, and must be adapted to ODE models.…”
Section: Discussionmentioning
confidence: 99%
“…As methods which are tailored a problem class tend to outperform black box solutions and since parameter estimation of ODE models is a bounded field, accounting for the specific structure can lead to substantial improvements (Froehlich et al, 2018;Schmiester et al, 2019). Studies have to be performed, which aim at a better understanding of the properties of this problem class, such as how non-identifiable parameters translate into uncertainties of model predictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To benchmark our local optimization methods, we used the interior-point optimizer Ipopt (64), which combines a limited-memory BFGS scheme with a line-search approach (44). In previous studies (54), since such interior-point optimizers have shown to be among the most competitive methods for local optimization of large-scale ODE systems (54; 62).…”
Section: Parameter Optimizationmentioning
confidence: 99%
“…Parameter estimation was performed using the parPE C++ library (54), which provides the means for parallelized objective function evaluation and optimization of ODE models generated by the AMICI ODE-solver toolbox (16) using optimizers such as Ipopt (64). In our studies, we used Ipopt version 3.12.9, running with linear solver ma27 and L-BFGS approximation of the Hessian matrix and extended parPE with the mini-batch algorithms described above.…”
Section: Implementation Of Parameter Estimation Using the Toolboxes Amentioning
confidence: 99%